The Massachusetts General Hospital Handbook of Behavioral Medicine : A Clinician's Guide to Evidence-based Psychosocial Interventions for Individuals with Medical Illness - Vranceanu, Ana-Maria; Greer, Joseph A.; Safren, Steven A. (Springer International Publishing : Imprint: Humana Press, 2017)
This text outlines the importance of biopsychosocial factors in improving medical care, and illustrates evidence-based, state-of-the-art interventions for patients with a variety of medical conditions. Each chapter is focused on a particular health concern or illness, which is described both in terms of prevalence and frequent psychological and psychiatric comorbidities that may present to clinicians working with these populations. Consistent with evidence-based care, information on the efficacy of the treatments being described is presented to support their continued use. To accommodate the needs of clinicians, we describe population specific approaches to treatment, including goal settings, modules and skills as well as strategies to assess and monitor progress. To facilitate learning, each chapter contains one or more case examples that explicate the skills described to convey change within a behavioral medicine protocol. Each chapter also includes resources in the form of books and websites to gain additional knowledge and detail as needed. Authors are experts in the field of each chapter, ensuring that information presented is recent and of high quality.
Keywords: Medicine.; Public health.; Primary care (Medicine).; Psychiatry.; Psychology.; elektronické knihy; electronic books